Small-sided games in elite soccer: Does one size fit all? - Lacome, M.; Simpson, B. M.; Cholley, Y.; Lambert, P.; Buchheit, M. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To compare the peak intensity of typical small-sided games (SSGs) with those of official matches in terms of running demands and mechanical work (MechW) over different rolling average durations and playing positions. Methods: Data were collected in 21 players (25 [5] y, 181 [7] cm, and 77 [7] kg) belonging to an elite French football team. SSG data were collected over 2 seasons during typical training sessions (249 files, 12 [4] per player) and official matches (n=12). Players` locomotor activity was recorded using 5-Hz Global Positioning System. Total distance (m), high-speed distance (HS, distance above 14.4 km/h, m), and MechW (a.u.) were analyzed during different rolling average periods (1-15 min). The SSGs examined were 4v4+goalkeepers (GKs), 6v6+GKs, 8v8+GKs, and 10v10+GKs. Results: Peak total distance and HS during 4v4, 6v6, and 8v8 were likely-to-most likely lower than during matches (effect size: -0.59 [±0.38] to -7.36 [±1.20]). MechW during 4v4 was likely-to-most likely higher than during matches (1-4 min; 0.61 [±0.77] to 2.30 [±0.64]). Relative to their match demands, central defenders performed more HS than other positions (0.63 [±0.81] to 1.61 [±0.52]) during 6v6. Similarly, central midfielders performed less MechW than the other positions during 6v6 (0.68 [±0.72] to 1.34 [±0.99]) and 8v8 (0.73 [±0.50] to 1.39 [±0.32]). Conclusion: Peak locomotor intensity can be modulated during SSGs of various formats and durations to either overload or underload match demands, with 4v4 placing the greatest and the least emphasis on MechW and HS, respectively. Additionally, in relation to match demands central defenders and central midfielders tend to be the most and least overloaded during SSGs, respectively.